KONSEPSI DAKWAH DALAM PEMBANGUNAN MASYARAKATMADANI INDONESIA (REFLEKSI ATAS REALITAS DAKWAH RASULULLAH MEMBANGUN MASYARAKAT MADINAH) - Abdul Rasyid Masri (TASÂMUH, 2017)
Nowadays, the world is more open and almost without any boundaries which brings about what is called open society. It is about to happen due to the era of information which takes place in every single country will be potentially giving the impact to the worldwide. This condition represents to people’s life who live in a global village. The concequence of this condition makes people to open their eyes of how important on the human rights and the commitment in developing their human-beings which are plural, open, advance, fair, equal, democratic, and modern, but they are still in to the values of local wisdom which are spiritual, moral, and civilized. The Madani citizens or civil society is the product of awareness of human rights and the commitment to build up the world in peace, restful, safety, and welfare to all people around the world. This concept is a kind of Rasullulah Saw’s. Dakwah reality whom He gets success to put the basic principles of Moslem people’s life in Madinah which portray about plurality, tolerance, open, democratic, fair, welfare, and civilization. The concept of how to be a citizen and to be a state turns trully the inspiration out for scholars and scientists in looking for modern and progressive society within the values of Ilahia spirituality and solidarity.